1997
DOI: 10.1002/hep.510260229
|View full text |Cite
|
Sign up to set email alerts
|

Histological findings in chronic hepatitis C with autoimmune features

Abstract: struction. 11 In other instances, they may identify individuals To evaluate the histological findings in patients with who respond adversely to interferon therapy, [12][13][14][15][16] and who chronic hepatitis C and autoimmune features, liver tissue might benefit from corticosteroid treatment. [17][18][19] In these latter specimens from 60 patients were graded under code for indicases, the autoimmune features may characterize a subgroup vidual features and composite patterns that denoted autoimwith immune-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 46 publications
4
56
0
1
Order By: Relevance
“…In most cases, titers are usually low, and cases with positive serologies are in general histologically indistinguishable from those without detectable antibodies. However, patients with an autoimmune overlap syndrome in whom liver biopsies reveal features of both chronic hepatitis C and inflammatory features charac teristic of AIH are occasionally encountered [4] . The treatment of patients with HCV/AIH overlap syndrome has until recently been challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, titers are usually low, and cases with positive serologies are in general histologically indistinguishable from those without detectable antibodies. However, patients with an autoimmune overlap syndrome in whom liver biopsies reveal features of both chronic hepatitis C and inflammatory features charac teristic of AIH are occasionally encountered [4] . The treatment of patients with HCV/AIH overlap syndrome has until recently been challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The higher age of our CH-C patients with ACA may have been responsible for the more progressive disease. On the other hand, Czaja and Carpenter [36] noted that CH-C patients with autoantibodies, including ANA and/or SMA, had higher HAI scores and a lower frequency of hepatic steatosis than CH-C patients lacking these autoantibodies. We confirmed that both hepatic fibrosis and inflammation in patients with CH-C seropositive for ANA were significantly more severe than that those in patients with CH-C seronegative for ANA ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…The degrees of grading are classified from A0 to A3. We also evaluated hepatic steatosis, bile duct damage, and lymphoid follicles, which are histological characteristics of CH-C [32][33][34][35][36][37]. The revised scoring system for a diagnosis of AIH, which was proposed by the International Autoimmune Hepatitis Group [38], was applied to each patient with CH-C seropositive for ACA in order to rule out a diagnosis of AIH.…”
Section: Histological Assessmentsmentioning
confidence: 99%
“…The Ishak system is funded based on viral hepatitis, mainly describing the intensities of inflammatory activities and structural progression of the liver diseases. However, in the histology of AIH, interface hepatitis, plasma cells infiltration, rosettes and emperipolesis are typical histological features [32,33]. A recent study suggests that emperipolesis and rosette formation are superior histological predictors of AIH than classic hallmark features, such as interface hepatitis and plasma cells infiltration [34].…”
Section: The Treatment Targets In Aihmentioning
confidence: 99%